PREDICTING CONSUMER PERCEPTION AND ITS IMPACT ON PURCHASE INTENTION FOR RESIDENTIAL PROPERTY MARKET - Tsun Hoe, Jeremy Tsang; Dastane, Omkar; Selvaraj, Karthik (Journal of Technology Management and Business, 2018)
The objective of this study is to investigate the effects of customer perceived value on customer purchase intention in the residential property market in Malaysia. The research proposes extension of Seth et al., 1991 model for property market by including relational aspect of the value as an added new parameter. Explanatory research design approach is used in this study with primary data collection through questionnaire survey of 172 respondents using convenience sampling method. The collected data and results are then analysed using SPSS 22 for Demographic analysis, Normality and Reliability test, Data Distribution. Finally, Pearson correlation analysis and Regression test is done to find the correlation between any two variables and relationship among the variables. The analysis indicated overall positive significant relationship with epistemic value being the highest among all. Regression analysis indicated functional value, social value, relational value, conditional value, and epistemic value shows positive significant effects on customer purchase intention while emotional value shows positive insignificant effect on customer purchase intention.The research is useful for marketers and researchers to understand perceived value based customer purchase intention for residential property sector among Malaysians and the tested model will be of great utility to property developers to devise appropriate value proposition based on consumer perceived value.Â